Load Balancing in WDM Network with Single and Multiple Lightpath Additions - Sumathi, M.; Vanathi, P.T. (Malaysian Journal of Computer Science, 2008)
Reconfiguration of a Wavelength Division Multiplexed (WDM) optical network is considered for varying traffic demands in the network. Reconfiguration is carried out with the aim of optimizing the objective function and minimizing the number of lightpath changes. This ensures the effective utilization of the network resources with minimum disruption to the network. In this paper, we present a new approach in which lightpaths with less traffic are considered for deletion during setup of a new lightpath. This increases the probability of setting up a new lightpath and decreases the value of the objective function; namely the congestion. Extensive simulation has been carried out for different traffic patterns. The congestion of the network and the number of lightpath changes has been studied. It is shown that deletion of lightpaths to free resources while setting up a new lightpath largely improves the congestion of the network. For slow varying traffic patterns, addition of one or two lightpaths minimized the congestion considerably. On the other hand, for rapid varying traffic patterns, minimizing load on one link might not considerably reduce congestion in the network. Therefore, multiple lightpath additions can enable decongesting multiple lightpaths in a single reconfiguration stage and balance the load in the network.